PENGAWASAN RETRIBUSI PARKIR DI KOTA PONTIANAK - Hikmah E.01108077, Syarifah Nurul (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Research on the supervision of parking charges in the town of Pontianak case study in the city of Pontianak Dipenda aims to identify and describe the implementation of the direct and indirect supervision by the Revenue of Pontianak on parking fees. The method used in this research is descriptive, where this type of study is intended to describe or depict the state of the object of research is happening at the present time based on the facts that appear or as they are. Based on the interview, indicated that the city government through the Revenue quite serious in order to supervise the collection of parking fees in the city of Pontianak. Based on the information submitted by the legislative party, shows that there is a difference between kenterangan submitted by the Revenue to the legislative Pontianak. Based on the interview with the Head of Revenue Determination of Pontianak, the information obtained from the monitoring that is done, is through control functions parking levy revenue report, for the year ideally potential park levy in Pontianak was Rp 5 billion more. Thus it can be said that the addition of a significant levy will be obtained if the additions are from compulsory levies individual carrying on business activities or compulsory levy the parking lot. Keywords: Supervision of direct and supervision of indirect.Â